Improvement of simulation of fine inorganic PM levels through better descriptions of coarse particle chemistry. (February 2015) - Trump, Erica R.; Fountoukis, Christos; Donahue, Neil M.; Pandis, Spyros N.
Abstract: Atmospheric chemical transport models (CTMs) have often serious difficulties reproducing the observed aerosol nitrate levels. We hypothesize that one of the reasons for these errors is their treatment of the competition between the accumulation and coarse-mode particles for the condensing nitric acid. The hybrid mass transfer method is used in the CTM PMCAMx to test this hypothesis. The simulation approach combines the dynamic calculation of mass transfer to coarse-mode particles while maintaining computational efficiency by assuming that the fine mode particles are in equilibrium. The resulting model is applied to Europe and evaluated for the period of May 2008 against ground-based and airborne Aerosol Mass Spectrometer measurements from the EUCAARI campaign. PMCAMx using the default equilibrium approach to calculate the partitioning of semi-volatile PM components between the gas and particle phases seriously overpredicts PM1 nitrate levels especially for locations in which there were relatively high coarse-mode particle concentrations (significant sea-salt or dust concentrations). This shortcoming was especially apparent for the Mace Head site in Ireland, where a large amount of nitrate was associated with sea-salt. The improved simulation of the coarse-mode particle chemistry results in significant improvement of the predictions of PM1 nitrate and ammonium. Sea-salt emissions in areas with high nitric acid levels reduce the PM1 nitrate concentrations. Highlights: Sea-salt particles in polluted areas cause reductions in submicron PM nitrate. Overprediction of fine nitrate due to inability to describe fine-coarse competition. A hybrid dynamics scheme leads to significant improvement of nitrate performance.